2007
DOI: 10.1017/s0007114507682944
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a high walnut and high cashew nut diet on selected markers of the metabolic syndrome: a controlled feeding trial

Abstract: We investigated the effects of a high walnut diet and a high unsalted cashew nut diet on selected markers of the metabolic syndrome. In a randomized, parallel, controlled study design, sixty-four subjects having the metabolic syndrome (twenty-nine men, thirty-five women) with a mean age of 45 (SD 10) years and who met the selection criteria were all fed a 3-week run-in control diet. Hereafter, participants were grouped according to gender and age and then randomized into three groups receiving a controlled fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 54 publications
8
111
1
Order By: Relevance
“…We felt that food provision was the best way to ensure high adherence to the dietary principles, but our design fell short of the conventional approach to a controlled feeding study in a few respects. We were not able to admit participants for a hospital stay or metabolic ward for the duration of the study [23], we could not provide cooked meals for participants [24], and we did not have the facilities to have participants eat at least 1 meal per day on site [22]. Notwithstanding these challenges, provision of food without observation of participant eating occasions or inpatient admission has been shown to result in high adherence to dietary advice in settings similar to ours [21].…”
Section: Discussionmentioning
confidence: 99%
“…We felt that food provision was the best way to ensure high adherence to the dietary principles, but our design fell short of the conventional approach to a controlled feeding study in a few respects. We were not able to admit participants for a hospital stay or metabolic ward for the duration of the study [23], we could not provide cooked meals for participants [24], and we did not have the facilities to have participants eat at least 1 meal per day on site [22]. Notwithstanding these challenges, provision of food without observation of participant eating occasions or inpatient admission has been shown to result in high adherence to dietary advice in settings similar to ours [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have found a significant reduction in fasting insulin (Casas-Agustench et al, 2011;Tapsell et al 2009) or a significant improvement in insulin resistance (Casas-Agustench et al, 2011). However, none have reported a significant reduction in glycated proteins as a marker of long-term glycemic control (Lovejoy et al, 2002;Scott et al, 2003;Tapsell et al, 2004;Estruch et al, 2006;Mukuddem-Petersen et al, 2007;Casas-Agustench et al, 2011;Tapsell et al, 2009;Ma et al, 2010). In light of recent evidence showing that the combination of the 2 h post-meal glucose levels and fasting blood glucose allow for better estimation of risk both for diabetes and CVD than the fasting blood glucose alone (Sorkin et al, 2005;International Diabetes Federation, 2007); further studies that examine the effect of nuts on post-meal glycemia are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A Mediterranean diet supplemented with 30 g of mixed nuts (walnuts, almonds and hazelnuts) per day also showed beneficial effects on the lipid profile compared with advice on a low-fat diet in diabetic and non diabetic participants in the PREDIMED study, a randomized trial of dietary intervention for the primary prevention of cardiovascular disease [80]. Of note, two randomized trials that used cashews or walnuts [81] and mixed nuts [82] compared to control diets in obese patients with the metabolic syndrome failed to show the predictable cholesterol lowering-effect, which supports the findings of the pooled analysis [69] (Figure 3) regarding the inverse association between cholesterol responses to nut feeding and BMI. There may be a mechanistic explanation for decreased lipid responsiveness to dietary intervention in patients with the metabolic syndrome.…”
Section: Nut Feeding Trials With Outcomes On Cardiovascular Risk Fmentioning
confidence: 99%